Gendered Informality in Egyptian Beauty’ Salons Egyptian Female Manicurists Who Cannot Afford the Beauty Price - Amer, Hager (AUC Knowledge Fountain, 2013)
This thesis analyzes the social world of beauty salons and the lives of Egyptian female beauty workers. Through an ethnographic analysis of the everyday interactions inside the beauty salons, this thesis presents the dynamics of labor relations and class formations. The aim of my research is to bring the social world of the salon into life. I hope to demonstrate a move away from the traditional studies of the beauty industry that highlight women insecurities about their bodies and their experiences in meeting the beauty standards. It is also not my intent to investigate the relation between physical appearance and women’s chances in securing better jobs. As a result of the two previous mentioned reason s, women desires for beauty services have increased dramatically. My goal then is to learn about the female beauty workers who serve those women in meeting the standards of beauty. It is my attempt to show how the gendered spaces of salons are used as sites of reproducing feminized social divisions. I am particularly concerned of the new identities that beauty female workers construct in the beauty salons and what influence does the salon location have on shaping those new identities. Studying beauty salons offers a rich site of observing gendered labour power relations inside the workplace. I analyze labour dynamics and hierarchy of authority inside the beauty salon. Labour dynamics are analyzed through the investigation of patterns of interactions among female beauty workers, clients and employers. I want to move beyond theoretical debates about service work in general to a more concrete analysis of the everyday lives of beauty workers. I decided to focus my study on those workers in particular not only because they have been overlooked by theorists but also because workers themselves do not comprehend the importance of engaging their labor dynamics in public debates. In addition, studying the dynamics of work in Egyptian beauty salons, offer new ways to think about different gendered meanings that are projected in the workplace that favor male workers while devalue female workers. Since female beauty workers’ services are always perceived as doing the dirty work, it is thus essential to explore their strategies of coping and resistance.